2017
DOI: 10.1093/ofid/ofx163.723
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Viral Loads in Patients with Co-infections vs. Single-virus Infections

Abstract: Background Molecular testing for respiratory viruses in clinical practice is common, often with multiple viruses detected. Viral load has been correlated with illness severity, but correlation of co-detection of viruses and viral load is less clear. We sought to compare cycle threshold (Ct) values, a marker inversely related to viral load, between single vs. co-detection of common respiratory viruses. Methods Children &lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…We then observed that compared with RSV mono-detections, samples tested positive for both RSV and another respiratory pathogen (especially if viral) showed significantly lower viral loads. These findings are in line with a pediatric study conducted during the 2015/16 season: Ct values in RSV single detections were on median 1.5 points lower (25.5 vs. 27.0; p = 0.05) than in RSV co-detections [45]. This observation may be explained by a negative viral inference that has been described for RSV co-infections with influenza A virus, rhinovirus and metapneumovirus [46].…”
Section: Discussionsupporting
confidence: 90%
“…We then observed that compared with RSV mono-detections, samples tested positive for both RSV and another respiratory pathogen (especially if viral) showed significantly lower viral loads. These findings are in line with a pediatric study conducted during the 2015/16 season: Ct values in RSV single detections were on median 1.5 points lower (25.5 vs. 27.0; p = 0.05) than in RSV co-detections [45]. This observation may be explained by a negative viral inference that has been described for RSV co-infections with influenza A virus, rhinovirus and metapneumovirus [46].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, compared with RSV mono-infections, samples tested positive for both RSV and another respiratory pathogen showed signi cantly lower viral loads. These ndings are in line with a pediatric study conducted during the 2015/16 season: Ct values in RSV single infections were on median 1.5 points lower (25.5 vs 27.0; p = 0.05) than in RSV co-detections [39]. This observation may be explained by a negative viral inference that has been described for RSV co-infections with in uenza A virus, rhinovirus and metapneumovirus [40].…”
Section: Discussionsupporting
confidence: 89%